Design and Implementation of Data and Voice Redundancy and Line Aggregation for VOIP with multiple links - Tun Oo, Tun; Aaron Don, Africa (International Journal of Engineering and Technology, 2018)
In the previous wired PSTN (Public Switched telephone network), ADSL system has used to get the Internet. In the present, VOIP (Voice Over Internet Protocol) technology is used for communication to use internet by using packet switching technique. PBX (Private Branch Exchange) was launched to substitute over common PSTN systems. In old telephone network, PSTN is more consumed phone bills or oversea costs than VOIP talk service. In this paper, the VOIP is used redundancy technologies by going the performance secure network paths about some security techniques to secure a network. Ethernet gateway redundancy is based on the concept of redundancy group. A redundancy group can contain one or more bridge groups located on the same or different gateways. A redundancy group can operate in two modes. The first one, which is the default mode, is active-passive. In active-passive mode, only one bridge group is active and all others are in hot-standby state. In case the active bridge group fails, another member from the same redundancy group is selected and activated. In active-active mode, all bridge groups are active and load balancing is enabled. Load balancing allows the user to distribute the load of IB nodes among all bridge groups of the redundancy group. In case of a bridge group failure, the load of the IB nodes is redistributed among the remaining bridge groups.
Keywords: ADSL; HSRP; OSPF; PSTN; PBX; VOIP